PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR PKN SISWA KELAS V SDN 5 TALANG KELAPA - Erlina; Saleh Hidayat; Widiasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of the Flipped Classroom learning model on the civics (PKN) learning outcomes of fifth-grade elementary school students, to determine the effect of independent learning on the civics learning outcomes of fifth-grade elementary school students, and to determine the effect of the Flipped Classroom learning model and independent learning on the civics learning outcomes of fifth-grade elementary school students at SD Negeri 5 Talang Kelapa. The results showed that learning with the Flipped Classroom model was more effective than the conventional model in improving students' civics learning outcomes. The Flipped Classroom learning model and students' independence in learning together have a positive and significant influence on learning outcomes.